Liquidity Shortages and Banking Crises - DIAMOND, DOUGLAS W.; RAJAN, RAGHURAM G. (Journal of Finance, 2005)
ABSTRACT We show in this article that bank failures can be contagious. Unlike earlier work where contagion stems from depositor panics or contractual links between banks, we argue that bank failures can shrink the common pool of liquidity, creating, or exacerbating aggregate liquidity shortages. This could lead to a contagion of failures and a total meltdown of the system. Given the costs of a meltdown, there is a possible role for government intervention. Unfortunately, liquidity and solvency problems interact and can cause each other, making it hard to determine the cause of a crisis. We propose a robust sequence of intervention.